A cradle-to-grave life cycle assessment of high-voltage aluminum electrolytic capacitors in China. (10th October 2022) - Zhang, Cheng; Jing, Junfeng; Yun, Liu; Zheng, Yu; Huang, Haihong
Abstract: Aluminum electrolytic capacitors (AECs) are widely used in electric circuits with various functions of filtering, power storage, decoupling, and circuit smoothing. High-voltage AECs can meet the requirements of high-voltage circuit applications, but they also aggravate the energy and environmental burden on capacitor production and use. The environmental performance of high-voltage AECs has not been well investigated, which weakens the manufacturers' ability to continuously reduce their negative environmental impacts. A cradle-to-grave life cycle assessment (LCA) of high-voltage AECs was performed to evaluate the environmental impacts and identify the corresponding environmental hotspots. According to the ReCiPe2016 method, fossil depletion, climate change, and photochemical ozone formation (ecosystems) are the main contributors to their environmental problems. The electricity used (798, 545 kWh per 100, 000 capacitors) and the raw material aluminum ingots (5130 kg per 100, 000 capacitors) are the environmental hotspots for high-voltage AECs' life cycle, which account for 94.1% of fossil consumption, 94.7% of greenhouse gas emission, and 94.9% of photochemical smog. It is of great significance to improve the area-specific capacitance of aluminum anode foil and the comprehensive electrical performance of high-voltage AECs to reduce their environmental impacts. This work would provide a benchmark to make informed eco-design decisions regarding the environmental consequences of alternative materials, design, manufacturing, and application for high-voltage AECs in the future. Highlights: A cradle-to-grave life cycle assessment is performed for high-voltage AECs. Fossil depletion, climate change, photochemical smog are key impact categories. Electricity and aluminum ingots are environmental hotspots for high-voltage AECs. Eco-design concerns area-specific capacitance of anode foil & electrical properties. The study benefits rebuilding the green industrial chain of high-voltage AECs.